Discovering computers & Microsoft Office 2013 a fundamental combined approach - Vermaat, Misty; Freund, Steven M. (Shelly Cashman series, 2014)
Combining computer concepts material from the best-selling Discovering Computers and step-by-step instruction on Office applications from Microsoft Office 2013, this title delivers the best of Shelly Cashman in one book for your Introduction to Computers course.